Crystal structure of the transcriptional regulator Rv1219c of Mycobacterium tuberculosis. (10th March 2014) - Kumar, Nitin; Radhakrishnan, Abhijith; Wright, Catherine C.; Chou, Tsung‐Han; Lei, Hsiang‐Ting; Bolla, Jani Reddy; Tringides, Marios L.; Rajashankar, Kanagalaghatta R.; Su, Chih‐Chia; Purdy, Georgiana E.; Yu, Edward W.
Abstract: The Rv1217c–Rv1218c multidrug efflux system, which belongs to the ATP‐binding cassette superfamily, recognizes and actively extrudes a variety of structurally unrelated toxic chemicals and mediates the intrinsic resistance to these antimicrobials in Mycobacterium tuberculosis . The expression of Rv1217c–Rv1218c is controlled by the TetR‐like transcriptional regulator Rv1219c, which is encoded by a gene immediately upstream of rv1218c . To elucidate the structural basis of Rv1219c regulation, we have determined the crystal structure of Rv1219c, which reveals a dimeric two‐domain molecule with an entirely helical architecture similar to members of the TetR family of transcriptional regulators. The N‐terminal domains of the Rv1219c dimer are separated by a large center‐to‐center distance of 64 Å. The C‐terminal domain of each protomer possesses a large cavity. Docking of small compounds to Rv1219c suggests that this large cavity forms a multidrug binding pocket, which can accommodate a variety of structurally unrelated antimicrobial agents. The internal wall of the multidrug binding site is surrounded by seven aromatic residues, indicating that drug binding may be governed by aromatic stacking interactions. In addition, fluorescence polarization reveals that Rv1219c binds drugs in the micromolar range. Abstract : Interactive Figure 1A ;Interactive Figure 1B